Artemisinin-resistant Plasmodium falciparum Kelch13 mutant proteins display reduced heme-binding affinity and decreased artemisinin activation - Abdur Rahman; Sabahat Tamseel; Smritikana Dutta; Nawaal Khan; Mohammad Faaiz; Harshita Rastogi; Jyoti Rani Nath; Kasturi Haldar; Pramit Chowdhury; Ashish; Souvik Bhattacharjee (Communications Biology)
Abstract The potency of frontline antimalarial drug artemisinin (ART) derivatives is triggered by heme-induced cleavage of the endoperoxide bond to form reactive heme-ART alkoxy radicals and covalent heme-ART adducts, which are highly toxic to the parasite. ART-resistant (ART-R) parasites with mutations in the Plasmodium falciparum Kelch-containing protein Kelch13 (PfKekch13) exhibit impaired hemoglobin uptake, reduced yield of hemoglobin-derived heme, and thus decreased ART activation. However, any direct involvement of PfKelch13 in heme-mediated ART activation has not been reported. Here, we show that the purified recombinant PfKelch13 wild-type (WT) protein displays measurable binding affinity for iron and heme, the main effectors for ART activation. The heme-binding property is also exhibited by the native PfKelch13 protein from parasite culture. The two ART-R recombinant PfKelch13 mutants (C580Y and R539T) display weaker heme binding affinities compared to the ART-sensitive WT and A578S mutant proteins, which further translates into reduced yield of heme-ART derivatives when ART is incubated with the heme molecules bound to the mutant PfKelch13 proteins. In conclusion, this study provides the first evidence for ART activation via the heme-binding propensity of PfKelch13. This mechanism may contribute to the modulation of ART-R levels in malaria parasites through a novel function of PfKelch13.